Public perception and acceptance of driverless buses in Yichang, China - Zeng, Yi; Tan, Mou Leong (Penerbit Universiti Kebangsaan Malaysia, 2025)
Previous research on driverless cars has predominantly focused on large cities in developed regions, with limited attention given to the acceptance of driverless buses in small and medium-sized cities. This study conducted a questionnaire survey involving 306 citizens from the Xiling District of Yichang City, analyzing the data using the structural equation model. The research expanded the traditional technology acceptance model by introducing three additional factors influencing public acceptance of driverless buses: perceived risk, perceived value, and perceived usefulness. Additionally, three secondary factors such as social impact, image, and result demonstrability were incorporated into the framework. The findings revealed that 69 participants (22.55%) fully accepted driverless buses, 117 participants (38.24%) were relatively accepting, 111 participants (36.27%) held a neutral stance, and only 9 participants (2.94%) were completely opposed. Young people and highly educated individuals demonstrated greater interest in learning about driverless buses. Social impact and perceived usefulness were identified as having a significant positive influence on public acceptance, while image and result demonstrability positively affected perceived usefulness. In contrast, perceived risk negatively impacted acceptance levels. As Yichang currently lacks driverless bus services, understanding local citizens' perceptions and acceptance is essential before promoting and implementing such services. This study provides valuable insights and a reference framework for the introduction and promotion of driverless buses in the city.